Effects of Trichoderma asperellum on growth stimulation in sweet pepper (Capsicum annum) variety Nathalie in greenhouse - Brenes-Madriz, Jaime (2019)
The use of Trichoderma fungus species is frequently used in biological control, where it was initially applied for its mycoparasitic and antibiotic properties. Numerous publications have also demonstrated its capacity to colonize the roots and their multiple favorable effects on crops. For Costa Rica there are no references that mention the use of secondary metabolites to increase production in sweet peppers. The objective of this research was to compare the effect of secondary metabolites present in a Trichoderma asperellum’s cultured filtrated in the stimulation of growth in sweet pepper (Capsicum annum var Nathalie) in protected environments. Treatments were evaluated at different concentrations of T. asperellum and its biofiltrates, in sweet pepper seedlings of the variety. The effects obtained with the application of T. asperellum on the stimulation of growth indicate that the use of this biocontroller has a major impact on the nursery stage. The treatment of T50 (T. asperellum 50%) was the best option during the two years of analysis in the elongation of the root, promoted an increase in the biomass of the root, besides it promoted an increase in the biomass of the root and the foliar area. However, the use of this microorganism in the greenhouse in the stage of productivity did not show significant differences between treatments, although a good foliar development of the plants compared with the control was observed.